2019
DOI: 10.3390/economies7030073
|View full text |Cite
|
Sign up to set email alerts
|

Bioeconomy: Markets, Implications, and Investment Opportunities

Abstract: In order to achieve the objectives of the Paris Climate Change Agreement, the conversion of our economy, which is still dominated by fossil carbon, to the bioeconomy model must be completed by 2050. This requires a shift from oil, gas and coal to agricultural, forestry and marine raw materials and will affect the global processing chains for energy, fuels and chemicals. However, the land required for the production of raw materials is competing with the production of food and animal feed. In addition, future l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 47 publications
1
27
0
3
Order By: Relevance
“…The multiple regression analysis concluded that the model was valid and correctly specified and the renewables were significant indicators of low carbon levels in all 27 EU countries, since the values of the estimated coefficients of the regression model were significantly different than zero and most of the variation of CO 2 emissions in EU countries was explained by the model. The results of the paper confirm recent studies of renewable energy impact on low carbon levels [47][48][49][50][51][52][53]. In addition, the novelty of this study resides in the fresh outlook taken for a set of 27 EU countries for the period 2008-2017, in order to assess the interaction between renewables and CO 2 emissions.…”
Section: Discussionsupporting
confidence: 79%
“…The multiple regression analysis concluded that the model was valid and correctly specified and the renewables were significant indicators of low carbon levels in all 27 EU countries, since the values of the estimated coefficients of the regression model were significantly different than zero and most of the variation of CO 2 emissions in EU countries was explained by the model. The results of the paper confirm recent studies of renewable energy impact on low carbon levels [47][48][49][50][51][52][53]. In addition, the novelty of this study resides in the fresh outlook taken for a set of 27 EU countries for the period 2008-2017, in order to assess the interaction between renewables and CO 2 emissions.…”
Section: Discussionsupporting
confidence: 79%
“…As several global crises are interrelated, 8 the bioeconomy's positive impacts can be compounded and far‐reaching 4,5 …”
Section: Scope Of the Bioeconomy In Mitigating Major Global Crisesmentioning
confidence: 99%
“…Although the bioeconomy is considered to mitigate several global sustainability crises, it has certain challenges, barriers, and controversies (Figs 2 and 3). 5,18–20 In Kircher's opinion, the transition to the bioeconomy is much more challenging than the transition from a pre‐modern bioeconomy to the current fossil carbon‐based economy 21 …”
Section: Current Debate Barriers and Challenges In Developing The Bioeconomymentioning
confidence: 99%
See 1 more Smart Citation
“…All opportunities and risks must be taken into account in development of bioeconomy in Slovakia. There is no clear way of implementing the bioeconomy strategy, as bioeconomy is a part of broader policy focused on green growth, new industrial and agriculture policy and a fossil fuels-independent society [7].…”
Section: Introductionmentioning
confidence: 99%